2016
DOI: 10.1021/acs.analchem.6b03473
|View full text |Cite
|
Sign up to set email alerts
|

Cathode Photoelectrochemical Immunosensing Platform Integrating Photocathode with Photoanode

Abstract: Generally, photoanode-based photoelectrochemical immunoassay possesses obvious photocurrent response and lower detection limit for ideal sample detection, but it has the inherent imperfection of poor anti-interference capability for real sample detection. Photocathode-based immunoassay can well avoid the intrinsic drawback of photoanode-based immunoassay, but it has low photocurrent response resulting in less good sensitivity. Herein, a promising new cathode photoelectrochemical immunosensing platform integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(67 citation statements)
references
References 40 publications
0
67
0
Order By: Relevance
“…12,21,22 In other words, p-type semiconductors are more stable than n-type semiconductors toward oxidation reactions. 23 As a popular p-type semiconductor, NiO (nickel oxide) has been widely used in the eld of sensors, catalyzers and solar cells due to its good stability, unique electrochemical performance and excellent catalytic properties. 20,24 BiOI (bismuth oxyiodide) is an ideal p-type photosensitizer with a narrow band gap ($1.7 eV) that possesses a wide visible light absorption range.…”
Section: Introductionmentioning
confidence: 99%
“…12,21,22 In other words, p-type semiconductors are more stable than n-type semiconductors toward oxidation reactions. 23 As a popular p-type semiconductor, NiO (nickel oxide) has been widely used in the eld of sensors, catalyzers and solar cells due to its good stability, unique electrochemical performance and excellent catalytic properties. 20,24 BiOI (bismuth oxyiodide) is an ideal p-type photosensitizer with a narrow band gap ($1.7 eV) that possesses a wide visible light absorption range.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional single-analyte immunosensor, the simultaneous multianalysis is more accurate and precise in clinical applications because it can quantitatively detect a panel of biomarkers in a single run with improved diagnostic specificity . Moreover, the multianalysis of cancer biomarkers can simplify the analytical procedure, enhance the detection throughput, and decrease the detection cost .…”
Section: Introductionmentioning
confidence: 99%
“…With the ever-growing demand for future sensing, there have been continuous efforts to exploit novel techniques with ingenious signaling strategies. Self-powered sensors, a rapidly developing concept, eliminate the common necessity of the external power sources and permit detection without the application of any voltage bias between the cathode and anode. , Such unique characteristics, along with the simple fabrication process, miniature size, and low cost, make them promising candidates for the diagnosis of human disease, especially as battery-less portable devices. Using semiconductors, a self-powered photoelectrochemical (PEC) biosensor is a newly developed and promising method that offers good sensitivity, portability, and the possibility of miniaturization and integration. Currently, because of the development of nanoscience and nanotechnology, more interest has been focused on the design and applications of functional semiconductor species for innovative self-powered PEC biosensors. , In the quest for achieving the desired performance and proper stability, judiciously designed heterostructures consisting of two semiconductors are being considered as favorite photoelectrode schemes. The existing literature has also demonstrated different heterostructures as effective tools for extending the absorbance to the visible region and improving photogenerated separation of charge carriers with increased lifetimes. However, consistently, appropriate band gap, proper band edge alignment with each other and with the redox potential of the electron donor/acceptor, minimal lattice mismatch, high stability, and ideal integration with the biorecognition events are the fundamental requirements for the construction of an efficient PEC biosensor system. To date, reported heterostructures for PEC biosensing have mainly focused on the coupling of various n-type TiO 2 species [nanoparticles (NPs), nanotubes (NTs), or nanowires (NWs) with n-type Cd-chalcogenide (S, Se, and Te) quantum dots (QDs)], leading to the development of different photoanodes. , For self-powered PEC biosensing, significantly, Zhang et al reported a self-powered sensing platform using Ni­(OH) 2 /CdS/TiO 2 , a hemin–graphene nanocomposite, and glucose as the photoanode, the photocathode, and a model analyte, respectively…”
mentioning
confidence: 99%
“…In spite of their fascinating characteristics, study of this domain lags greatly. Recently, p-type BiOI and CuInS 2 were used to construct the cathodic PEC aptasensor and cathodic PEC immunoassay, respectively. With respect to the heterojunction photocathodes, at present, only limited work exploited the use of p-type species for the construction of a p–n heterojunction comprised of, e.g., p-type BiOI and n-type TiO 2 proposed by our group. , Obviously, novel p-type-based heterostructures and their smooth application in efficient self-powered PEC bioanalysis are highly desirable.…”
mentioning
confidence: 99%